Identification and Screening of Selective WEE2 Inhibitors to Develop Non‐Hormonal Contraceptives that Specifically Target Meiosis. Issue 45 (5th December 2019) - Hanna, Carol B.; Yao, Shan; Martin, Mat; Schönbrunn, Ernst; Georg, Gunda I.; Jensen, Jeffrey T.; Cuellar, Rebecca A. D.
Abstract: We used a progressive elimination strategy to identify oocyte‐specific WEE2 kinase inhibitors for potential non‐hormonal contraceptives that target meiosis. Beginning with an in‐house library of over 300, 000 compounds, virtual high throughput screening identified 57 WEE2 inhibitors with preferential predicted binding over the somatic variant WEE1. Seven compounds were further evaluated in vitro by enzyme‐linked immunosorbent assay to measure biochemical inhibition on WEE1 and WEE2 phosphorylation of CDK1. To assess specificity, we evaluated WEE2‐mediated inhibition of meiosis using in vitro oocyte fertilization, and WEE1‐mediated inhibition of mitosis using a somatic cell proliferation assay. Our results from these assays identified three candidates for further development: 6‐(2, 6‐dichlorophenyl)‐2‐((4‐(2‐(diethylamino)ethoxy) phenyl)amino)‐8‐methylpyrido[2, 3‐d]pyrimidin‐7(8H)‐one (2), 6‐(2, 6‐dichlorophenyl)‐8‐methyl‐2‐((4‐morpholinophenyl)amino)pyrido[2, 3‐d]pyrimidin‐7(8H)‐one (12), and 3‐((6‐(2, 6‐dichlorophenyl)‐8‐methyl‐7‐oxo‐7, 8‐dihydropyrido[2, 3‐d]pyrimidin‐2‐yl)amino)benzoic acid (16) . Abstract : Finding inhibitors to fertilization: WEE2 Kinase is an oocyte specific protein that permits fertilization to occur through phosphorylation of CDK1 (CDC2). Selective inhibitors to WEE2 represent a unique class of novel non‐hormonal contraceptives for women. Virtual high throughput screening of drug libraries combined with in vitro interrogation of selected compounds was used to identify potential drug candidates.